Formal and informal institutional legacies and inward foreign direct investment into firms: Evidence from China - Zhang, Chenjian (Journal of International Business Studies, 2022)
This paper explores the influence of informal institutional legacy on contemporary foreign direct investment (FDI). This study is situated in the context of China’s Treaty Port Era (1842–1943). Hypotheses are posited and tested related to how the treaty port policies and overseas Chinese communities of cities established during that period created formal and informal institutional legacies that positively influence the likelihood and volume of contemporary inward FDI firms receive. This research suggests that despite and because of the Cultural Revolution’s traumatic shock, informal institutions helped formal institutions morph into informal rules and thus created a lingering legacy effect. Drawing on a longitudinal sample of Chinese firms’ data and historical materials that provide information about treaty ports and overseas Chinese communities, this study finds supporting evidence that informal institutional legacy is important for contemporary FDI and brings history back into the international business literature. This study provides practical implications by suggesting that, given the increasing turbulence and uncertainties in emerging markets and transnational economies, building and maintaining connections with transnational community actors of these countries could take advantage of the informal institutions to mitigate risks and sustain international business activities. International investors could also benefit by investing in locales with rich transnational community connections.